2021
DOI: 10.1182/blood.2020007591
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-497/195 is tumor suppressive and cooperates with CDKN2A/B in pediatric acute lymphoblastic leukemia

Abstract: We previously identified an association of rapid engraftment of patient-derived leukemia cells transplanted into NOD/SCID mice with early relapse in B-cell precursor acute lymphoblastic leukemia (BCP-ALL). In search for the cellular and molecular profiles associated with this phenotype, we investigated the expression of microRNAs (miRNAs) in different engraftment phenotypes and patient outcomes and found high miR-497/195 expression in patient-derived xenograft samples with slow engraftment, derived from patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…Furthermore, we found that the expression of miR-195 was increased significantly when the A549 and H1975 cell lines were treated with d -limonene. This miRNA reported by us and others before can suppress the growth of lung cancer and other cancers, including acute lymphoblastic leukaemia, triple-negative breast, liver, glioblastoma, prostate, stomach and colorectal cancers [ 54 59 ]. We also found that miR-195 could directly bind to the mRNAs of SREBF1 , FASN and ACACA in lung cancer cells resulting in decreases in lipid droplet formation induced by PM 2.5 exposure.…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, we found that the expression of miR-195 was increased significantly when the A549 and H1975 cell lines were treated with d -limonene. This miRNA reported by us and others before can suppress the growth of lung cancer and other cancers, including acute lymphoblastic leukaemia, triple-negative breast, liver, glioblastoma, prostate, stomach and colorectal cancers [ 54 59 ]. We also found that miR-195 could directly bind to the mRNAs of SREBF1 , FASN and ACACA in lung cancer cells resulting in decreases in lipid droplet formation induced by PM 2.5 exposure.…”
Section: Discussionmentioning
confidence: 81%
“…MiR-195-5p is a multitarget regulator involved in various aspects of cancer cell behavior (31). It can regulate the cell cycle and inhibit the growth of leukemia cells; its expression is increased and is an important prognostic factor (32). Furthermore, stable expression of miR-195-5p in a mouse xenograft model of ovarian cancer significantly reduced tumor growth, increased tumor doubling time, and improved overall survival (33).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, miRNAs stand out as prospective therapeutic targets against CSCs, necessitating an attentive consideration of the multifaceted spectrum of miRNA functionalities. Illustratively, miR-760, miR-205, miR-497, miR-136, let-7 family, among several others, have demonstrated the capability to suppress certain cancer types and exert negative modulation over CSCs. Conversely, miR-146, miR-221/222, etc.…”
Section: Strategies For Sniping Cscsmentioning
confidence: 99%